2009
DOI: 10.4103/0970-0218.51236
|View full text |Cite
|
Sign up to set email alerts
|

Health and social problems of the elderly: A cross-sectional study in Udupi Taluk, Karnataka

Abstract: Background:Change in socio-economic status and various health problems adversely affect an individual's way of life during old age.Objectives:To study the health and social problems of the elderly and their attitude towards life.Materials and Methods:Descriptive study carried out in the Field practice area of the Department of Community Medicine in South India. A total of 213 elderly patients (60 years old and above) who attended the outreach clinics were interviewed using a pre-tested schedule. Findings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
104
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 2 publications
18
104
5
Order By: Relevance
“…Banker K et al, Lena et al and Shankar R et al reported joint pains to be 60.2%, 41.3% & 57.8% respectively. 5,10,12 Cataract and hearing impairment constituted 24.8% and 10.7% respectively, similar finding was reported by Purthy AJ where prevalence of cataract was 24.6% and hearing impairment was 14.3%.…”
Section: Morbidity Profilesupporting
confidence: 77%
See 3 more Smart Citations
“…Banker K et al, Lena et al and Shankar R et al reported joint pains to be 60.2%, 41.3% & 57.8% respectively. 5,10,12 Cataract and hearing impairment constituted 24.8% and 10.7% respectively, similar finding was reported by Purthy AJ where prevalence of cataract was 24.6% and hearing impairment was 14.3%.…”
Section: Morbidity Profilesupporting
confidence: 77%
“…The present study was conducted rural area, in which majority (70.8%) were in the age group of 60-69 years and females constituted large part of study subjects (62.2%).Similar observations were noted in various studies done by Sushma Tiwari et al, Lina et al and Anita Rani et al [9][10][11] Most of study subjects were illiterates (94.5%) and were currently employed (67.8%). However study by Srinivasan et al & Lena et al reported illiteracy to be 4.8% & 45.1% respectively.…”
Section: Socio-demographic Profilesupporting
confidence: 71%
See 2 more Smart Citations
“…Rapid socio-demographic changes like urbanization, nuclearization of family, migration and dual career families are making care of the elderly more and more of a personal and social problem in India. 4 Beyond biological changes, ageing is also associated with other life transitions such as retirement, relocation to more appropriate housing, and the death of friends and partners. 2,3 The growth of the elderly population present a new challenge to health system and social support networks in many less developed countries where populations are becoming old before they become wealthy.…”
Section: Introductionmentioning
confidence: 99%